Body Shame dan Gangguan Makan Kajian Meta-Analisis - Lisya - Chairani (Faculty of Psychology Universitas Gadjah Mada, 2018)
The number of person with eating disorders is increasing almost all over the world. Theexact cause of an eating disorder is difficult to determine. The feeling of shame caused by negativejudgments on one’s body has a positive correlation to the emergence of pathological eatingbehavior. Furthermore, the position of body shame as a variable in research on eatingdisorders is still inconsistent in some studies, consequently, it is placed as a mediatingvariable to self-objectification. This study attempted to see whether there is a directcorrelation between body shame and eating disorders using meta-analysis procedure. Theanalysis of sampling error and measurement error made on 34 studies from 21 articles. Theresult of the analysis showed that body shame and eating disorder are strongly correlated(r=0.547) with α = 0.05.